Agatha Christie's Miss Marple. Set two, volume three. They do it with mirrors. [videorecording (DVD)] - Christie, Agatha, 1890-1976; Hickson, Joan, 1906-1998; Gallaccio, George (Miss Marple., 1991)
Miss Marple takes a trip to Stonygates to discover why her friend is being poisoned. When shots are fired in a darken room, Miss Marple deduces the identity of the killer but not how it was done.